SISTEM BASIS DATA PERSEDIAAN UNTUK PENGENDALIAN INTERNAL PERSEDIAAN PADA PERUSAHAAN JASA PENDINGIN RUANGAN - ARDELIA, DEVINA (Berkala Ilmiah Mahasiswa Akuntansi)
corporate goals. Inventory cycle is one cycle that is important, this is because the cycle is related to the operations of the company and support the company’s main activity. PT MMJ is a service company engaged in the service air conditioning. This company doesn’t have a data base system, causing inventory item record does not match the physical inventory. Preparation of inventory reports which takes long enough to record and report the error to be done manually can save time in the process. The purpose of this research is to design a computerized inventory system that will be expected to help solve problems facing the company. This type of research conducted is a case study and using this type of qualitative data. Data analysis techniques is the evaluation of systems and procedures that is evaluation of the company’s organizational structure, evaluation and control of internal corporate documents, creation of data flow diagrams and database, creations of the REA, perform system requirements analysis, and manufacture of access restrictions, and system interface computerization. In this study will make an inventory database system for inventory cycle at PT MMJ. The results of this study show that the separation of functions must be done to improve internal control. With the inventory of information system design based on this data. Expected errors in recording inventory in the warehouse can be reduced and can produce the required information quickly and accurately.